MEDICAL ASPECTS OF SUPPORTING CHILDREN WITH AUTIC SPECTRUM DISORDERS - M MEHDI; E.L SHOPSHA (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
Autism spectrum disorder is a childhood mental illness characterized by communication disorders, uneven intellectual development, repetitive behaviors and mental retardation. These behavioral symptoms appear in early childhood. The exact cause of this disease in most children has not yet been clarified. Treatment for people with this condition includes behavioral management and, in some cases, medication. The disease can occur in a person early in life, but depending on the severity of the symptoms, the disease may not appear until school age. Among the main features of autism spectrum disorder is the presence of problems with persistent disorders of social communication and interaction, limited interests and activities. The article provides information on symptoms, diagnosis, severity of the disease, treatment procedures for autism spectrum disorders.